PELATIHAN KONSELOR SEBAYA PADA SISWA KELAS XI SMAN 1 WONOGIRI MENGGUNAKAN ZOOM MEETING DI ERA PANDEMI COVID-19 - Edmawati, Mahmuddah Dewi; Maynawati, Aldila Fitri Radite Nur; Hidayati, Awik (Jurnal Terapan Abdimas, 2021)
Abstract. The purpose of peer counselor training activities for class XI students of SMAN 1 Wonogiri using a zoom meeting in the Covid-19 pandemic era is to provide information about peer counselors and provide peer counselor skills to students at SMAN 1 Wonogiri. This training also provides information on guidance and counseling services, increases the ability to become peer counselors, and makes peer counselors an extension of counseling services in schools to help solve peer problems. Peer counselor training were carried out in 4 stages. Phase 1, by sharing and questioning, several training participants were asked to share their experiences while receiving guidance and counseling services during the Covid-19 pandemic. Stage 2 is the provision of material about peer counselors. The material is delivered in the form of lectures on peer counselor materials, discussions, provides examples of peer counselor activities through videos and carries out practices in the form of role-playing as a counselor and counselee. Stage 3 is the practice and implementation of peer counselor guidance and stage 4 is to evaluate the results of the peer counselor practice. The results of peer counselor training include improving the image of counseling guidance services through peer counseling activities, providing interpersonal skills to students, increasing knowledge and skills to become peer counselors so that students can become partners for guidance and counseling teachers.  Abstrak. Tujuan dari kegiatan pelatihan konselor sebaya pada siswa kelas XI SMAN 1 Wonogiri menggunakan zoom meeting di era pandemi covid-19 adalah memberikan informasi mengenai konselor sebaya dan memberikan ketrampilan konselor sebaya kepada siswa di SMAN 1 Wonogiri. Pelatihan ini juga memberikan informasi mengenai layanan bimbingan dan konseling, meningkatkan kemampuan menjadi konselor sebaya, dan menjadikan konselor sebaya sebagai perpanjang tangan layanan BK di sekolah untuk membantu memecahkan permasalahan teman sebaya. Pelatihan konselor sebaya dilaksanakan dalam 4 tahap. Tahap 1 dengan dengan sharing dan tanya jawab beberapa peserta pelatihan diminta untuk menyampaikan pengalaman selama menerima layanan bimbingan dan konseling di masa pandemi covid-19. Tahap 2 yaitu pemberian materi mengenai konselor sebaya. Materi disampaikan dalam bentuk ceramah mengenai materi konselor sebaya, diskusi, memberikan contoh kegiatan konselor sebaya melalui video dan melaksanakan praktik dalam bentuk role-playing sebagai konselor dan konseli. Tahap 3 yaitu praktik dan pendampingan pelaksanaan konselor sebaya dan tahap 4 yaitu mengevaluasi hasil dari praktik konselor sebaya. Hasil kegiatan pelatihan konselor sebaya antara lain meningkatkan citra layanan bimbingan konseling melalui kegiatan konseling sebaya, memberikan ketrampilan interpersonal kepada siswa, menambah pengetahuan dan keterampilan menjadi konselor sebaya sehingga siswa dapat menjadi partner guru bimbingan dan konseling.